Radiographic diagnosis of pediatric condilar fractures. Insufficient conventional radiographic protocol. Report of two clinical cases - Guzmán-Z., Carmen Lucía; Posso-LL., María del Rosario; Bonilla, Jorge (Revista Facultad de Odontología Universidad de Antioquia, 2009)
Maxilla-Facial trauma is the main etiologic factor in jaws and facial fractures. In children, mandibular fractures are one of the main reasons of facial and developmental deformities because they can affect the main facial bony structures. This paper presents two cases of maxilla facial trauma in children. The main lesions were diagnosed as intra-articular fractures of the Temporo Mandibular Joint with compromise of the condyle. The conventional radiographic protocol provided insufficient information for the diagnosis.